Trace Eyeblink Conditioning is Impaired in α7 but not in β2 Nicotinic Acetylcholine Receptor Knockout Mice - Brown, Kevin L.; Comalli, David M.; De Biasi, Mariella; Woodruff-Pak, Diana S. (Frontiers in Behavioral Neuroscience, 2010)
Nicotinic acetylcholine receptors (nAChRs) are essentially involved in learning and memory. A neurobiologically and behaviorally well-characterized measure of learning and memory, eyeblink classical conditioning, is sensitive to disruptions in acetylcholine neurotransmission. The two most common forms of eyeblink classical conditioning – the delay and trace paradigms – differentially engage forebrain areas densely-populated with nAChRs. The present study used genetically modified mice to investigate the effects of selective nAChR subunit deletion on delay and trace eyeblink classical conditioning. α7 and β2 nAChR subunit knockout (KO) mice and their wild-type littermates were trained for 10 daily sessions in a 500-ms delay or 500-ms trace eyeblink conditioning task, matched for the interstimulus interval between conditioned stimulus and unconditioned stimulus onset. Impairments in conditioned responding were found in α7 KO mice trained in trace – but not delay – eyeblink conditioning. Relative to littermate controls, β2 KO mice were unimpaired in the trace task but displayed higher levels of conditioned responding in delay eyeblink conditioning. Elevated conditioned response levels in delay-conditioned β2 KOs corresponded to elevated levels of alpha responding in this group. These findings suggest that α7 nAChRs play a role in normal acquisition of 500 ms trace eyeblink classical conditioning in mice. The prominent distribution of α7 nAChRs in the hippocampus and other forebrain regions may account for these genotype-specific acquisition effects in this hippocampus-dependent trace paradigm.